2017
DOI: 10.18805/ajdfr.v36i03.8973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of legume supplementation on physical and textural characteristics of ready to eat cereal bars

Abstract: The present study was carried out to find the effect of legume supplementation on Physical and textural characteristics of ready to eat cereal bars. Therefore, physical and textural parameter of ready to eat cereal bars was analyzed. Results showed that the length, width and thickness of the bars ranged between 9.69±0.29 to 10.02±0.01 cm, 4.52±0.02 to 4.90±0.05 cm and 0.85±0.04 to 0.99±0.01cm. Whereas spread ratio, per cent spread, volume, weight and density was found to range between 4.90±0.11 to 5.30±0.30, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
2
2
0
1
Order By: Relevance
“…The volume of plantain-based snack bars increased linearly with the addition of rice bran, from 22.21 cm 3 for PSO to 23.63 cm 3 for PSRO, while density decreased in the same manner, from 0.71 g/cm 3 (PSRO) to 0.72 g/cm 3 (PSO). The results are comparable to those reported by Yadav and Bhatnagar (23), who found that the volume of RTE cereal bars increased linearly with the addition of legume ours, while density reduced in a similar manner. The ndings are also similar with Simona et al (29), who found that the volume of gluten-free biscuits increased linearly as the amount of soy our increased, while the density reduced in the same manner.…”
Section: Physical Characteristics Of Snack Barsupporting
confidence: 90%
“…The volume of plantain-based snack bars increased linearly with the addition of rice bran, from 22.21 cm 3 for PSO to 23.63 cm 3 for PSRO, while density decreased in the same manner, from 0.71 g/cm 3 (PSRO) to 0.72 g/cm 3 (PSO). The results are comparable to those reported by Yadav and Bhatnagar (23), who found that the volume of RTE cereal bars increased linearly with the addition of legume ours, while density reduced in a similar manner. The ndings are also similar with Simona et al (29), who found that the volume of gluten-free biscuits increased linearly as the amount of soy our increased, while the density reduced in the same manner.…”
Section: Physical Characteristics Of Snack Barsupporting
confidence: 90%
“…In similar studies, an increase in hardness of mushroom fortified bread and cake samples with increasing level of mushroom fortification have also been reported earlier (Eissa et al 2007;Majeed et al 2017). Whereas, on the contrary, legume flour incorporation has reported to cause a decrease in hardness of cereal bars (Yadav and Bhatnagar, 2017). However, as per the sensory evaluation, the scores for texture and mouth-feel of energy bars were recorded to be most acceptable for 20 % level of mushroom powder incorporation (Table 4).…”
Section: Textural Qualitysupporting
confidence: 71%
“…The texture properties determined were the hardness and crispness of the fruit-nut-bars. They were measured in terms of the maximum peak force and number of peaks during the first compression cycle with the texture analyzer ("Stable Micro Systems", Winopal, Germany) according to Yadav and Bhatnagar (2017) with the following settings: Pre-Test Speed: 2 mm/s; Test Speed: 1 mm/sec; Post-Test Speed: 10 mm/s; Force: 10 g; Trigger Force: 10 g; Probe: P/5; 5 mm Dia Cylinder (Figure 3).…”
Section: Textural Profile Analysismentioning
confidence: 99%